Water Crisis in Mexico.Reflections on Its Shortage and Management (International Journal of Scientific Research and Management (IJSRM), 2023)
Mexico is experiencing a water crisis particularly in the central and northern regions of the country due to increasing droughts. Millions of liters of water are used by the processed food industry or soft drink or beer companies, the agricultural and livestock industry among others, these are the economic activities that consume the most water. Therefore, it is important that the water crisis experienced in Mexico should not be addressed based on the lack of rain, the implementation of effective public policies for the supply of water that respond to the expectations of the population should also be considered. Another aspect that must be taken into account is that the Mexican legislation that regulates the exploitation or use of national waters, as well as their distribution, control and preservation of their quantity and quality, has to be reviewed, renewed and adapted to the current needs of the country to guarantee the human right to water. In this context and using an inductive-deductive methodology, a documentary review of national and international legislation was carried out, as well as literature related to the water crisis affecting Mexico. In short, it is important to state that the management of water resources must be based on principles of solidarity, collective access and equity, which are by definition incompatible with any commercial approach motivated by private benefit and public benefit. Definitely, the implementation of public policies that effectively combat water scarcity in Mexico must be linked to the management, protection and infrastructure for the distribution and storage of water. This includes regulating water extraction and promoting sustainable practices in all sectors of the economy.